Protocol for the purification of protected carbohydrates: toward coupling automated synthesis to alternate-pump recycling high-performance liquid chromatography. Issue 90 (24th October 2016) - Nagy, Gabe; Peng, Tianyuan; Kabotso, Daniel E. K.; Novotny, Milos V.; Pohl, Nicola L. B.
Abstract : Analytical techniques that can be coupled to automated oligosaccharide synthesis platforms are needed to purify to homogeneity protected carbohydrates at levels of ≥99.5% purity. Abstract : Given recent advances in automated oligosaccharide synthesis, analytical techniques that can be coupled to a synthetic framework are needed to not just identify but also purify to homogeneity protected carbohydrate compounds at levels of ≥99.5% purity. Herein, an alternate-pump recycling high-performance liquid chromatography (R-HPLC) method has been developed to allow purification of protected carbohydrates at levels of ≥99.5% purity.